The General Effects of Dioxins on Livestock Feeding - Süleyman Çalışlar; Mesut Karaman (Turkish Journal of Agriculture: Food Science and Technology)
Dioxins is one of the chemicals groups that cause liver toxicity, live weight reduction, immune suppression, reproductive impairments, eggshell thinning, birth defects, cancers and death in animals. The 2,3,7,8- tetrachlorodibenzo-p-dioxin (TCDD) is the most poisonous environmental chemical and many studies were showed high dosage of TCDD affects all animal group. Also TCDD increase cancer risk in human so this chemical described as carcinogenic by International Agency for Research on Cancer. Dioxins are stored in animal foods such as meat, milk, eggs and fish, because they are soluble in oil and remain in these products for many years. Dioxins can dissolve in fat and high stability therefore it can be infected to meat, milk, egg, and fish and store there for long time as a result people could be contained with dioxin during daily life. Animal feed additives such as organic acids, pH modifiers, starch, sugar, vegetable oil, fat, fruit and by-products of plant, kaolinite, rendering products, pelleting aids cause dioxin contamination. The maximum dioxin content in plant-origin feedstuffs and their by-products is 0.75 ng toxic equivalent/kg body weight. In this rewiew, the effects of dioxins on livestock feeding was examined.